America's Paul Revere - Forbes, Esther; Ward, Lynd, 1905-1985 (Boston, Houghton Mifflin company, 1946)
A biography of the patriot of the Revolution who had many trades, among them silver work, manufacture of copper, casting of bells, engraving, and dentistry.
Keywords: Revere, Paul, -- 1735-1818.; Statesmen -- Massachusetts -- Biography -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Biography -- Juvenile literature; Massachusetts -- Biography -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Biography